Arm and interarm abundance gradients in CALIFA spiral galaxies - Sánchez-Menguiano, L. (2017)
Spiral arms are the most singular features in disc galaxies. These structures can exhibit different patterns, namely grand design and flocculent arms, with easily distinguishable characteristics. However, their origin and the mechanisms shaping them are unclear. The overall role of spirals in the chemical evolution of disc galaxies is another unsolved question. In particular, it has not been fully explored if the H ii regions of spiral arms present different properties from those located in the interarm regions. Here we analyse the radial oxygen abundance gradient of the arm and interarm star forming regions of 63 face-on spiral galaxies using CALIFA Integral Field Spectroscopy data. We focus the analysis on three characteristic parameters of the profile: slope, zero-point, and scatter. The sample is morphologically separated into flocculent versus grand design spirals and barred versus unbarred galaxies. We find subtle but statistically significant differences betweenthe arm and interarm distributions for flocculent galaxies, suggesting that the mechanisms generating the spiral structure in these galaxies may be different to those producing grand design systems, for which no significant differences are found. We also find small differences in barred galaxies, not observed in unbarred systems, hinting that bars may affect the chemical distribution of these galaxies but not strongly enough as to be reflected in the overall abundance distribution. In light of these results, we propose bars and flocculent structure as two distinct mechanisms inducing differences in the abundance distribution between arm and interarm star forming regions.